1970
DOI: 10.2134/agronj1970.00021962006200020018x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen and Phosphorus Fertilization on Growth, Yield, and Cooking Characteristics of Rice1

Abstract: One greenhouse experiment and four field experiments were conducted during 1964–65 to determine (a) the effect of rate, time, and method of P fertilization on grain yield, yield components, and cooking quality estimation of rice, and (b) the existence of N × P interactions. Increasing P in 1964 increased lodging and reduced grain yields and 1,000 grain weight. In 1965 there was no influence of P rate. Preplant P produced darker green vegetation, broader leaves, and taller plants than did the midseason applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

1973
1973
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 1 publication
(1 reference statement)
1
20
1
Order By: Relevance
“…Nitrogen also plays a role in grain filling, improving the photosynthetic capacity, and promoting carbohydrate accumulation in culms and leaf sheaths (Mae, 1997). Earlier studies revealed that judicious and proper use of fertilizers can markedly increase the yield and improve the quality of rice (Place et al, 1970) Rice plants produced more number of productive tillers per hill as well as longest panicles where 120 kg nitrogen per hectare was applied. The lowest values of number of productive tillers per hill and shortest panicles were which recorded in control treatment receiving no fertilizer.…”
Section: Discussion-mentioning
confidence: 99%
“…Nitrogen also plays a role in grain filling, improving the photosynthetic capacity, and promoting carbohydrate accumulation in culms and leaf sheaths (Mae, 1997). Earlier studies revealed that judicious and proper use of fertilizers can markedly increase the yield and improve the quality of rice (Place et al, 1970) Rice plants produced more number of productive tillers per hill as well as longest panicles where 120 kg nitrogen per hectare was applied. The lowest values of number of productive tillers per hill and shortest panicles were which recorded in control treatment receiving no fertilizer.…”
Section: Discussion-mentioning
confidence: 99%
“…Nitrogen also plays a role in grain filling, improving the photo-synthetic capacity, and promoting carbohydrate accumulation in culms and leaf sheaths (Mae, 1997). Earlier studies reveal that judicious and proper use of fertilizers can markedly increase the yield and improve the quality of rice (Place et al, 1970). Given the importance of nitrogen fertilization on the yield in grain from the rice plant, it is necessary to know what the best dose is for each variety as well as its influence on components of yield and other agronomic parameters such as the cycle, plant height, lodging and moisture content of the grain, in order to obtain better knowledge of said productive response.…”
Section: Introductionmentioning
confidence: 99%
“…Fish stir up soil nutrients making them more available for rice. Nitrogen which is an essential plant nutrient being a component of amino acids, nucleic acids, nucleotides, chlorophyll, enzymes, and hormones is well achieved from the Fish faecal matter [7,8,10]. The Molluscs, insects which are harmful to Rice plants are controlled and killed by Fishes.…”
Section: Objectives and Advntages By Doing R Cum F Culturementioning
confidence: 99%
“…Integrated rice-fish farming results in mutual benefit to both rice and fish. Nitrogen which is an essential plant nutrient is also well provided by the fish excreta [8][9][10]. In addition, the aquatic weeds of rice also get reduced due to fish presence.…”
Section: Introductionmentioning
confidence: 99%